Assessment of the therapeutic potential of Hsp70 activator against prion diseases using in vitro and in vivo models - Zayed, Mohammed; Kim, Yong-Chan; Jeong, Byung-Hoon (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Prion diseases are deadly neurodegenerative disorders in both animals and humans, causing the destruction of neural tissue and inducing behavioral manifestations. Heat shock proteins (Hsps), act as molecular chaperones by supporting the appropriate folding of proteins and eliminating the misfolded proteins as well as playing a vital role in cell signaling transduction, cell cycle, and apoptosis control. SW02 is a potent activator of Hsp 70 kDa (Hsp70).In the current study, the protective effects of SW02 against prion protein 106-126 (PrP 106-126 )-induced neurotoxicity in human neuroblastoma cells (SH-SY5Y) were investigated.In addition, the therapeutic effects of SW02 in ME7 scrapie-infected mice were evaluated.The results showed that SW02 treatment significantly increased Hsp70 mRNA expression levels and Hsp70 ATPase activity (p < 0.01). SW02 also significantly inhibited cytotoxicity and apoptosis induced by PrP 106-126 (p < 0.01) and promoted neurite extension. In vivo, intraperitoneal administration of SW02 did not show a statistically significant difference in survival time (p = 0.16); however, the SW02-treated group exhibited a longer survival time of 223.6 ± 6.0 days compared with the untreated control group survival time of 217.6 ± 5.4 days. In addition, SW02 reduced the PrP Sc accumulation in ME7 scrapie-infected mice at 5 months postinjection (p < 0.05). A significant difference was not observed in GFAP expression, an astrocyte marker, between the treated and untreated groups.In conclusion, the potential therapeutic role of the Hsp70 activator SW02 was determined in the present study and may be a novel and effective drug to mitigate the pathologies 2 of prion diseases and other neurodegenerative diseases. Further studies using a combination of two pharmacological activators of Hsp70 are required to maximize the effectiveness of each intervention.